Development of methodology for geometric tolerances analyzing during assembly based on adaptation of mathematical apparatus of robot kinematics inverse problem - D. D. Primak; I. A. Volkov; V. B. Masyagin; R. L. Artykh (Омский научный вестник)
Information about the assembly process is directly influenced to the product accuracy. A modeling technique based on the schematization of the assembly process information for predict the product accuracy is proposed. Information about assembly deviations is displayed by the geometry deviations in contact points, the propagation of deviations between parts and the direction of deviations propagation. A schematic connection is established between the assembly process information and the deviations propagation information, a technique for precision assembly modeling include a method based on adapting the mathematical apparatus used in the kinematics of robots and a methodology for influencing of assembly deviations transitions.